Survey on geographic visual display techniques in epidemiology: Taxonomy and characterization - Lee, Lilian Yen Wei; Ag. Asri Ag. Ibrahim; Kashif Nisar; Zamhar Iswandono AwangIsmail; Ian Welch (2020)
Many works have been done on the topic of Geographic Visual Display with different objectives and approaches. There are studies to compare the traditional cartography techniques (the traditional term of Geographic Visual Display (GVD) without Human-Computer Interaction (HCI)) to Modern GIS which are also known as Geo-visualization, some literature differentiates and highlight the commonalities of features and architectures of different Geographic Visual Display tools (from layers and clusters to dot and color and more). Furthermore, with the existence of more advanced tools which support data exploration, few tasks are done to evaluate how those tools are used to handle complex and multivariate spatial-temporal data. Several test on usability and interactivity of tools toward user's needs or preferences, some even develop frameworks that address user's concern in a wide array of tasks, and others prove how these tools are able to stimulate the visual thought process and help in decision making or event prediction amongst decision-makers. This paper surveyed and categorized these research articles into 2 categories: Traditional Cartography (TC) and Geo-visualization (G). This paper will classify each category by their techniques and tasks that contribute to the significance of data representation in Geographic Visual Display and develop perspectives of each area and evaluating trends of Geographic Visual Display Techniques. Suggestions and ideas on what mechanisms can be used to improve and diversify Geographic Visual Display Techniques are provided at the end of this survey.